The effect of high protein enteral nutrition on protein status in acute stroke patients (Faculty of Medicine Universitas Indonesia, 2005)
The objective of this study was to determine the effect of high protein enteral nutrition on protein status in acute stroke patients. The subjects were divided into two groups using block randomisation, i.e. the intervention group that received high protein enteral nutrition (HPEN), and the control group that received enteral hospital diet. Thirty six out of 60 acute stroke patients had completed 7 days of follow-up. The results showed that HPEN have increased prealbumin level, decreased urinary creatinine excretion, and decreased the decline of albumin serum compared to the control group. (Med J Indones 2005; 14: 37-43) Keywords: albumin, prealbumin, urinary urea nitrogen, urinary creatinine, nitrogen balance